STRATEGI PEMASARAN RETAIL KONVENSIONAL UNTUK MENINGKATKAN VOLUME PENJULAN DI UD PODO ELENG SAWAHAN LENGKONG NGANJUK - Amrullah, Azam Fahmi (Universitas Nusantara PGRI Kediri, 2023)
This study basically aims to determine the implementation of marketing strategies at UD Podo Eleng Sawahan Lengkong Nganjuk. This research uses qualitative research methods, with data collection techniques through interviews, observation and documentation, so that then it can explain the marketing strategy on the object of this research. Thus the results of this study explain that increasing sales volume at UD above can be done by providing discounts on each sales product such as a minimum purchase of IDR 500,000, and feeding every blessed Friday with the aim of attracting customer interest. Besides that, the distribution channel is considered strategic enough so that it can provide convenience for consumers, thus UD Podo Eleng provides online ordering and direct delivery, this is done so that goods can be delivered right to consumers, as the level of comparison of sales results for the last 3 years shows that sales volume continues to increase.